How Korean middle school students see inventors: the images of the inventor - Lee, Eunsang; Kwon, Hyuksoo (International journal of technology and design education, 2019)
One distinguishing feature in terms of national curriculum revisions is the emphasis on invention education in the subject of technology. This study investigates how South Korean middle school students perceive inventors. A manufactured tool for testing and a checklist for evaluating images of inventors were created to assess drawings of 115 8th grade students. The final 108 surveys (from 52 male and 56 female students) were analyzed, and the results were quite similar to those of prior studies that examined how students picture scientists. This research confirmed that students had stereotypical images of inventors. Stereotypical elements that were not depicted in prior studies were also discovered. For example, tools such as spanners, hammers, and screwdrivers, which are used for building and fixing things, were proposed as symbols of research by students. Overcoming such stereotypical representations requires improving stereotypical images of inventors as they are presented in photos and figures of textbooks, developing and implementing educational programs that introduce relevant images of inventors, and changing teachers’ recognition.